Tailored postoperative treatment of prostate cancer: final results of a phase I/II trial. Issue 4 (November 2018) - Mantini, Giovanna; Siepe, Giambattista; Alitto, Anna; Buwenge, Milly; Nguyen, Nam; Farioli, Andrea; Schiavina, Riccardo; Catucci, Francesco; Deodato, Francesco; Fionda, Bruno; Frascino, Vincenzo; Macchia, Gabriella; et al.
Abstract Backgroud The European Organization for Research and Treatment of Cancer (EORTC) trial 22, 911 reported 74% 5-year biochemical disease-free survival (bDFS) in patients with prostate carcinoma treated with radical prostatectomy (RP) followed by postoperative radiotherapy (RT). This study aimed to improve these outcomes by using a combined-intensified-modulated-adjuvant treatment, including RT and hormone therapy (HT) after RP. Materials and methods This phase I/II trial treatment was designed to improve 5-year bDFS from 75 to 90%. Patients were consecutively enrolled using the following inclusion criteria: age < 80 years, histological diagnosis of prostate adenocarcinoma without known metastases, stage pT2-4N0-1, and Eastern Cooperative Oncology Group performance status of 0–2. All patients had at least one of these pathologic features: capsular perforation, positive surgical margins, seminal vesicle invasion, and pelvic lymph nodes involvement. A minimum dose of 64.8 Gy to the tumor bed was delivered in all patients. Depending on tumor characteristics at diagnosis, patients received a higher dose (70.2 Gy; 85.4%) and/or prophylactic pelvic lymph nodes irradiation (57.7%) and/or HT (69.1%). Biochemical relapse was defined as two consecutive rising prostate-specific antigen (PSA) values > 0.2 ng/ml. Results A total of 123 patients were enrolled in the study and completed the scheduled treatment. Median preoperative and postoperative PSA were: 8.8 and 0.06 ng/mL, respectively. The percentages of patients with pathologically involved nodes and positive resection margins were: 14.6% and 58.5%, respectively. With a median follow-up of 67 months (range: 37–120 months), the actuarial 5-year bDFS, local control, metastasis-free survival, and overall survival (OS) were: 92.9%, 98.7%, 96.1%, and 95.1%, respectively. Conclusion A higher 5-year bDFS (92.9%) was recorded compared to studies based on standard adjuvant RT, even though patients with nodal disease and detectable postoperative PSA were enrolled. Clinical end points, as long-term disease-free survival and OS, will require further assessments. (ClinicalTrials.gov: NCT03169933)